High-Accuracy Determination of Microsatellite Instability Compatible with Liquid Biopsies. (14th February 2020) - Silveira, Amanda Bortolini; Bidard, François-Clément; Kasperek, Amélie; Melaabi, Samia; Tanguy, Marie-Laure; Rodrigues, Manuel; Bataillon, Guillaume; Cabel, Luc; Buecher, Bruno; Pierga, Jean-Yves; Proudhon, Charlotte; Stern, Marc-Henri
Abstract: Background: Microsatellite instability (MSI) has recently emerged as a predictive pan-tumor biomarker of immunotherapy efficacy, stimulating the development of diagnostic tools compatible with large-scale screening of patients. In this context, noninvasive detection of MSI from circulating tumor DNA stands as a promising diagnostic and posttreatment monitoring tool. Methods: We developed drop-off droplet-digital PCR (ddPCR) assays targeting BAT-26, activin A receptor type 2A ( ACVR2A ), and defensin beta 105A/B ( DEFB105A/B ) microsatellite markers. Performances of the assays were measured on reconstitution experiments of various mutant allelic fractions, on 185 tumor samples with known MSI status, and on 72 blood samples collected from 42 patients with advanced colorectal or endometrial cancers before and/or during therapy. Results: The 3 ddPCR assays reached analytical sensitivity <0.1% variant allelic frequency and could reliably detect and quantify MSI in both tumor and body fluid samples. High concordance between MSI status determination by the three-marker ddPCR test and the reference pentaplex method were observed (100% for colorectal tumors and 93% for other tumor types). Moreover, the 3 assays showed correlations with r ≥ 0.99 with other circulating tumor DNA markers and their dynamic during treatment correlated well with clinical response. Conclusions: This innovative approach for MSI detection provides a noninvasive, cost-effective, and fast diagnostic tool, well suited for large-scale screening of patients that may benefit from immunotherapy agents, as well as for monitoring treatment responses.